Traffic accident monitoring system using radio frequency identification tools - Pardo, Eduardo Martin Estela (2022)
This article proposes a system that allows monitoring car accidents with the use of NFC technology. The solution is comprised of low-cost Radio Frequency Identification (RFID) tools integrated into a mobile and web application that interact with the Google Maps API for efficient monitoring. The car accident reporting process collects and sends data manually through different service channels, which generates delays and, in some cases, the receipt of erroneous data. The proposed solution automates the accident reporting process by storing data from the users involved in the RFID tags and displaying them in the mobile and web applications, when generating a new report. Also, our application interacts with the Google Maps API to show the exact location from where accidents are reported, in order to speed up the process of attention by the PNP. The validation was carried out in the city of Lima, Peru. Preliminary results yielded data showing a 94% reduction in the accident reporting process and a 94% reduction in the average data capture time by the National Police of Peru (PNP).